ICASSP 2022 - 2022 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2022
DOI: 10.1109/icassp43922.2022.9747109
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate and Oxygen Saturation Estimation from Facial Video with Multimodal Physiological Data Generation

Abstract: Video-based heart and respiratory rate measurements using facial videos are more useful and user-friendly than traditional contact-based sensors. However, most of the current deep learning approaches require ground-truth pulse and respiratory waves for model training, which are expensive to collect. In this paper, we propose CalibrationPhys, a self-supervised video-based heart and respiratory rate measurement method that calibrates between multiple cameras. CalibrationPhys trains deep learning models without s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…[81] Some machine learning-based approaches have been proposed to tickle the problem of traditional signal processing methods. Akamatsu et al [82] proposed MultiPhys and CNN models to simultaneously estimate heart rate and oxygen saturation from facial videos. In summary, there are two difficulties in the research and exploration of oxygen saturation measurement.…”
Section: Oxygen Saturationmentioning
confidence: 99%
“…[81] Some machine learning-based approaches have been proposed to tickle the problem of traditional signal processing methods. Akamatsu et al [82] proposed MultiPhys and CNN models to simultaneously estimate heart rate and oxygen saturation from facial videos. In summary, there are two difficulties in the research and exploration of oxygen saturation measurement.…”
Section: Oxygen Saturationmentioning
confidence: 99%
“…Deep learning techniques have achieved state-of-the-art performance for the remote measurement of physiological signs such as HR [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] and RR [36,[39][40][41][42][43][44][45][46][47]. However, remote SpO2 measurement is still in its infancy, with only a few papers using convolutional neural networks (CNNs) to predict SpO2 from RGB facial videos [48][49][50]. Additionally, most existing methods are evaluated on private self-collected datasets, preventing a fair comparison of algorithmic performance [51].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in this paper, we propose the use of EVM, as a preprocessing step to enhance the video content captured by the infrared camera. Recent research has explored and demonstrated various methods for estimating oxygen saturation levels using facial video with multimodal physiological data generation [19] or via DC and AC component extraction of a spatiotemporal map using facial videos [17].…”
Section: Introductionmentioning
confidence: 99%